The Financial Management of Stock in the Path of Allah in Achieving Economic Stability and Security - Alwadi, Hazem Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2025)
Allah has blessed us with a complete and comprehensive religion that is suitable for reforming all times and places. This religion includes a financial obligation, which is zakat, which is capable of solving all economic problems in a comprehensive and complete way, after diligence in the branches and keeping the fundamentals fixed. The diligence in the branches is by the Zakat House issuing its own currency, which can be called the Islamic Dinar, and its reserve is the national currency. The case of the Zakat House working on that and paying the dues of a stock in the way of Allah, which amounts to one-eighth of the Zakat proceeds, the following Findings can be reached: The stock in the Path of Allah contributes in achieving economic stability by curbing inflation, eliminating unemployment, and confronting any threat to the country from the north and east. This is achieved through: Financing the expenses of a stock in the way of Allah from the money issued by the Zakat Treasury. As for what the Ministry of Defense needs in terms of imports, foreign currencies are purchased from money changers, the Central Bank, or commercial banks with the money issued by the Zakat Treasury, as well as by presenting the collection of the Zakat proceeds for the coming year, and the donations collected for the Ministry of Defense from citizens, i.e. jihad with money, and by issuing Islamic bonds to be a good loan, this is to control the money supply and the speed of money circulation, which curbs inflation resulting from military operations. Eliminating unemployment: This is achieved by financing military projects, factories, bases and infrastructure from the allocations of the share in the way of God obtained from zakat and the collection of zakat for the coming year, and donations provided by citizens to be a financial jihad, and with a good loan by issuing Islamic bonds to finance the construction of projects, factories, bases and infrastructure and what the armed forces need in terms of construction, All of this contributes to employing the elements of production, including land, labor, capital, and organization, which reduces unemployment.
Keywords: Stock in the way of Allah; safe investment environment; economic stability; velocity of money; inflation; military expenditures